Reconstructing Past Arctic Faunal Communities Using Ancient DNA in Lake Sediment - Power, Matthew William Paul (Curtin University, 2022)
In this thesis, lake sediment cores collected from Baffin Island, Arctic Canada were investigated using sedimentary ancient DNA techniques. The data presented showcases the power of these techniques to document dramatic ecosystem changes of the past. Results document the responses of fauna to climactic change over a period of thousands of years in an effort to inform future changes to the Arctic system in the context of a rapidly warming world.